Pengaruh Metode Pembelajaran Role Reversal Question Terhadap Kemampuan Berfikir Kritis - Hadi Gunawan Sakti; Siti Nurannisa (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
The problem faced, especially in Indonesian language subjects, is that student learning outcomes in class are unsatisfactory, this is because the method of delivering material uses the lecture method which makes students bored and the learning process becomes uninteresting and monotonous. The aim of this research is to determine the influence of the Role Reversal Questions learning method on students' critical thinking abilities in class X Indonesian language subjects at SMKN 3 Mataram for the 2022/2023 academic year. The data collection method used in this research is tests as the main method, observation and documentation as complementary methods. The data analysis technique uses the t-test formula. In accordance with the results of the t-test calculation obtained through analysis, namely t-count = 3.88. Meanwhile, the t-table value is 1.706 with a significance level = 5%, namely 0.05%, with db = N-1 = 27-1= 26, which is 1.706. Thus it can be seen that the calculated t-value is greater than the t-table value (3.88>1.706). This means that the null hypothesis is rejected and the alternative hypothesis is accepted which states that there is an influence of the Role Reversal Questions Learning Method on Students' Critical Thinking Ability in Class X Indonesian Language Subjects at SMKN 3 Mataram for the 2022/2023 Academic Year. So it can be concluded that the results of this research are "significant".